2021
DOI: 10.1520/mpc20210034
|View full text |Cite
|
Sign up to set email alerts
|

Development of Marble Dust/Waste PET Based Polymer Composite Material for Environmental Sustainability: Fabrication and Characterizations

Abstract: Polyethylene terephthalate (PET) is available at a very low cost compared to the conventional methods of disposal. The reason for using marble dust is that it has good mechanical properties, and it is also a nonflammable compound. To develop the biocomposite, PET was allowed to mix with marble dust in a screwed extruder, and then its mechanical and physical properties were examined. Results indicate that the highest value of tensile strength was 14.5 MPa found at 15 wt. % of marble dust; the highest value of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We observed that the size of WMP particles differs and varies as per the range stated earlier. This distribution was also observed to be almost homogeneous to comply with the mixing phenomena that was performed during the fabrication [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…We observed that the size of WMP particles differs and varies as per the range stated earlier. This distribution was also observed to be almost homogeneous to comply with the mixing phenomena that was performed during the fabrication [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 79%
“…The increase in the flexural strength was because of the shear behaviour WMP provided in the composite. Upon loading the specimen, the particles of WMP deformed in the lateral direction and transferred the shear forces to the basalt fibre, which led to more considerable deformation in the lateral direction, which consequently increased the load applied and delayed the time of fracture [ 4 , 5 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several minified curves at around 3000 cm −1 to 2800 cm −1 . This minified broad spectrum is also a part of the –OH groups bond in the material [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. The other functional group present in the ABS material after the treatment with acetone was the aromatic compounds bond, as we can see peaks of the curves at around 1600 cm −1 to 1400 cm −1 .…”
Section: Findings and Discussionmentioning
confidence: 99%